THE PRACTICAL VALUE OF DETERMINING THE ERYTHROCYTE SERIES IN PATIENTS WITH COPD OF PROFESSIONAL ETIOLOGY - Levina, E.V.; Ivchuk, V.V.; Rubtsov, R.V. (World of Medicine and Biology, 2017)
The concentration of hemoglobin, the content of erythrocytes, the hematocrit index and the structural properties of erythrocytes in the blood of workers in the mining industry of patients with chronic obstructive pulmonary disease (COPD) of professional etiology of various severity were studied. It was found that most often changes in blood type of erythropoiesis and increased hemoglobin formation were registered in patients with COPD stage I. Blood hemoglobin concentration exceeded the norm in 35.9%, erythrocytes – in 46.1%, high hematocrit was in 46.1%, the volume of erythrocytes was increased – in 32.0% of cases. In patients with COPD II and III stage, a decrease in the frequency of detection of hyperhemoglobinaemia to 22.2%-22.4%, erythrocytosis to 26.8%-23.5%, high hematocrit to 14.1%-12.9%, an increase in volume of erythrocytes to 19.1%-21.2% of cases. Erythrocytosis in COPD patients is probably a favorable prognostic sign. It has an adaptationally compensatory character and depends on the severity of the disease.